KONTESTASI WACANA POLITIK IDENTITAS DALAM RUANG DIGITAL MENJELANG PEMILIHAN GUBERNUR SULAWESI TENGGRA - Iriyani Astuti Arief; Indra Lestari; Yunita Simatupang (Halu Oleo University, 2023)
This research aims to identify and analyze the contestation of identity political discourse that has developed in society's digital space ahead of the election for Governor of Southeast Sulawesi. In this research, the theories used are framing theory, the concept of public space, and the identity politics concept to find out why the community selects the Governor. Identity politics can arise based on a society’s ethnicity, religion, and culture. This is significant since the rise in community political participation in Southeast Sulawesi is heavily influenced by tribal factors. Meanwhile, the data collection technique used literature study with data analysis techniques that include three stages Data reduction, data presentation and conclusion. The research findings that the contestation of identity political discourse in the digital space ahead of the election for Governor of Southeast Sulawesi showed dynamics in the use of digital space, especially on social media Facebook and Instagram. The tribal phenomenon has become a hot topic of discussion in the digital space, as shown by the comments of supporters of the three gubernatorial candidates, namely Andi Sumangerukka (ASR), a Bugis tribe, Kery Saiful Konggoasa (KSK), and Lukman Abunawas (LA) a tolaki tribe. The tribal public mindset of Kendari city people can determine the map of political power, making them to select who is most ideal to be a leader in Southeast Sulawesi.